Pengaruh Penggunaan Quizizz sebagai Latihan Soal terhadap Hasil Belajar Siswa Kelas V SD - Moch Chabib Dwi Kurniawan; M. Misbachul Huda (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
The learning process during the Covid-19 pandemic has the potential to cause saturation in students. Variations in learning activities during the Covid-19 pandemic are a necessity for learning in elementary schools. Quizizz is a technology-based platform that has an interactive display and is attractive to the millennial generation. The use of quizzes in the learning process is an innovative effort made by the teacher. This study aims to determine the effect of using quizizz as a question practice platform on the learning outcomes of fifth grade elementary school students. This study used a quasi-experimental method with a pretest-posttest control group design. The sample was selected by random sampling method with a population of class V SDN Kepanjen II Jombang. Research data in the form of student learning outcomes obtained by test techniques. Data analysis using t test. The results showed that t count was greater than t table, so the research hypothesis was accepted. The use of quizizz as a question practice platform has a positive effect on learning outcomes of fifth grade elementary school students. The implication of this research is the need to use technology-based platforms in learning to create pleasant learning conditions in elementary schools.